(untitled) (Proceedings of Southern Federal University. Philology, 2014)
Key words: national policy, democratic tendencies in mass media, ethnographic review, journey, article. Russian national politics was widely criticized in the 19th-century journalism and literature. Democratic trends were reflected in satirical press and in the works of critical realism. Renowned writers and publicists disapproved the government measures aimed at the enslavement of Russian ethnic minorities. Stan’ko Alexander Ivanovich - Ph.D. of linguistics, professor of history of journalism dpt. of Southern federal university